The Role of Public and Domestic Based on Perspective Dr. Faqihuddin Abdul Kodir Through a Phenomenological Approach - Amalia, Nabila Nailil; Asbarin; Wilda Fitria, Risa Pramita; Lum'ah, Diana Durrotul (UIN Sulthan Thaha Saifuddin Jambi, 2022)
Stigmatization of Indonesian society who still uses the label of patriarchal culture by limiting the space, higher education opportunities and participation in the public sphere for women under the pretext of hadith understood by the editor of the dominance of women's stereotypes.This study aims to analyze the role of public and domestic for men and women based on the perspective of Dr. Faqihuddin Abdul Kodir through a phenomenological approach. This type of research is qualitative research with a literature study method and uses a phenomenological approach. The primary data sources in this study are women’s books (not sources of slander, while secondary data sources are books, journal articles, seminars, and online sites that are accurate and in line with this research). Data collection techniques used are observation and documentation. While the data analysis used deductive descriptive analysis. The results of this study are public and domestic roles for men and women based on the perspective of Dr. Faqihuddin Abdul Kodir through a phenomenological approach is not a sect that must be debated if using the Mubadala method. If the Mubadalah method is applied, then gender inequality such as a double burden will not occur if we adhere to the reciprocal and relational theory.